Original paperDIFFERENT RECOVERY METHODS AND MUSCLE PERFORMANCE AFTER EXHAUSTING EXERCISE: COMPARISON OF THE EFFECTS OF ELECTRICAL MUSCLE STIMULATION AND MASSAGE - Pinar, S.; Kaya, F.; Bicer, B.; Erzeybek, M.S.; Cotuk, H.B. (Biology of Sport, 2012)
In this study we assessed the influence of the three different recovery interventions massage (MSG), electrical muscle stimulation (EMS), and passive rest (PR) on lactate disappearance and muscle recovery after exhausting exercise bouts. Twelve healthy male sport students participated in the study. They attended the laboratory on five test days. After measurement of ·VO2max and a baseline Wingate test (WGb), the three recovery interventions were tested in random counterbalanced order. High intensity exercise, which consisted of six exhausting exercise bouts (interspersed with active recovery), was followed by MSG, EMS or PR application (24 minutes); then the final Wingate test (WGf) was performed. Lactate, heart rate, peak and mean power, rating of perceived exertion (RPE), and total quality of recovery (TQR) were recorded. In WGf mean power was significantly higher than in WGb for all three recovery modalities (MSG 6.29%, EMS 5.33%, PR 4.84% increase, p 0.05). The heart rate response and the changes in blood lactate concentration were identical in all three interventions during the entire protocol (p=0.817, p=0.493, respectively). RPE and TQR scores were also not different among the three interventions (p>0.05). These results provide further evidence that MSG and EMS are not more effective than PR in the process of recovery from high intensity exercise.